Strategic management factors within the organization of the tourism service business in the capital city of Prabang, Luang Prabang province, case study: hotel-resort business - PHANTOUAMATH, Poutthalack; HOONGSENGPHA, Soudtida; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to study the business conditions of the hotel-resort business in Prabang capital, to study the strategic management factors within the organization of the hotel-resort business in Prabang capital, and to study the marketing management strategic factors of the hotel-resort business in Prabang capital. The population used in the research was entrepreneurs or hotel-resort business executives within 74 business units. The research tool is a questionnaire with a reliability value of 0.986, the statistics used for data analysis are: frequency value, mean value, standard deviation and binary regression coefficient analysis. The research finds that: The operation condition of hotel-resort business in Luang Prabang are mostly business establishment by registration under the form of sole proprietorship, business establishment between 1 - 5 years, employing between 6 - 50 people, the main customers are internal customers, the provision of ancillary services is catering services. The sale of services through online social media is available. There is a marketing promotion through online social media. And all of the business are a business that has become a member of a business group/business project. The management factors within the organization found that the strategic factors of management within the organization as a whole are important to the operation of the hotel-resort business in the capital city of Prabang at many levels, which include: strategic factors are most important to business operations in the first order and followed by organizational structure factors are most important. In this form factors, work performance system factors, knowledge/skills factors, personnel factors and shared value factors are very important to business operations. The marketing management factor is given importance to be applied in the operation of the business as a whole at the highest level including: the service process factor, the service channel factor, the personnel factor, the price factor and the physical aspect management factor, which is the factor that the business gives importance to the operation at the most level. And for the service marketing management factor and the marketing promotion factor are the factors that the business gives importance to the performance at many levels.